Meningkatkan Kesadaran Bahaya Kejahatan Siber Melalui Sosialisasi Cyber Security Di SMKN 26 Jakarta - Nursiaga, Rahmat; Nana Mulyana; Imam Santoso; Toni Saidun Ali; Hadi Firmanyah; Alfonso Sabatani Quiko (Politeknik Penerbangan Indonesia Curug, 2025)
The use of technology is very important in everyday life, people are required to be able to adapt to technology because currently humans and technology are interrelated. The use of technology can simplify and help human activities but can also have negative impacts, one of which is Cyber ​​Crime (cyber threats). Most students often use online media for learning activities such as coordinating learning with teachers such as WhatsApp messages or interacting with social media such as Facebook, Instagram, Twitter, TikTok or other online media. Students often store information, both personal data and photos, on their social media accounts. Interactions with social media are vulnerable to Cyber ​​Crime attacks and students are less aware of this and do not know how to manage their social media accounts to avoid Cyber ​​Crime. Therefore, the aim of this community service is to provide awareness to student partners at SMKN 26 Jakarta of the importance of Cyber ​​Security in using the internet to avoid the risk of Cyber ​​Crime and to teach best practices in protecting sensitive data and personal information from unauthorized access. The methods used are lectures, discussions and quizzes to motivate students to take part in PKM. The results of this activity are based on the post test: 88% of students understand the importance of cyber security.